A Systematic Literature Review of Machine Learning Methods for Short-term Electricity Forecasting - Md Salleh N.S.; Suliman A.; Jorgensen B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Forecasting; Investments; Machine learning; Development investment; Energy prediction; Evaluation metrics; Long term planning; Machine learning methods; Metric evaluation; Resource planning; Systematic literature review; Learning algorithms